The Role of the Dayak Customary Council as a Local Policy Entrepreneurs in the Food Estate Agenda in Central Kalimantan - Farid Zaky Yopiannor; Syukur Muhaymin Adang Djaha (Yayasan Ilomata, 2026)
This paper examines the role of the Dayak Customary Council (DAD) as a local policy entrepreneur in the implementation of Indonesia's food estate program in Central Kalimantan. While the national policy has sparked debate regarding its socio-environmental impacts, the influence of indigenous actors on agenda-setting remains underexplored. This study investigates how DAD reframed the food estate as a development opportunity, utilized customary rituals to legitimize land conversion, and strategically aligned with the provincial government. Using a qualitative case study and process tracing methodology, data were gathered through interviews, document analysis, and field observations. The findings demonstrate that DAD performed a dual role as both a cultural mediator and a political actor, skillfully navigating between state interests and indigenous concerns. This study contributes to the theoretical understanding of hybrid governance by illustrating how indigenous institutions can act as key policy entrepreneurs in subnational policymaking. It emphasizes the importance of incorporating indigenous governance structures into the policy process. In practical terms, the findings highlight the need for policymakers to engage with indigenous institutions in development projects, ensuring the integration of local knowledge and values. Further research should explore the long-term socio-environmental impacts of such collaborations and how they influence policy outcomes across different regions in Indonesia.